Respon Pertumbuhan Bibit Alpukat terhadap Pemberian Pupuk Kandang Sapi dan NPK - Firgiyanto, Refa; Rohman, Fadil; Siswadi, Edi; Dinata, Gallyndra Fatkhu; Fajar, Rafli Toriq (Agropross : National Conference Proceedings of Agriculture, 2023)
Avocado is one of the most popular horticultural commodities because it has a delicious taste and high nutrition. In order to increase avocado production in Indonesia, nutrition management at each stage of cultivation is an aspect that needs attention. Appropriate fertilizer application needs to be started in the seedling phase to support plant growth to produce productive mature plants. Effective nutrition management can be done by integrating the application of organic fertilizers and inorganic fertilizers. Therefore, a study was conducted on the growth response of avocado seedlings to the application of cow manure and NPK. This study aimed to determine the effect of cow manure and NPK and its interaction on the growth of avocado seedlings. The research was conducted from August to October 2022 in Dukuh Mencek Village, Sukorambi, Jember, East Java. This study used a factorial randomized block design consisting of 2 factors. The first factor was the dose of cow manure which consisted of 4 levels, namely 0, 90, 181 and 272 g/plant. The second factor was the concentration of NPK which consisted of 3 levels, namely 7, 14 and 21 g/l. Each treatment combination was repeated 3 times so there were 36 experimental units. Observation variables included plant height, stem diameter, number of leaves and number of shoots. Observational data were analyzed using analysis of variance (ANOVA). The application of cow manure and NPK had no significant effect on all observation variables